Efektivitas Program Beasiswa Dari Zakat Selama Pandemi Covid-19 Pada Badan Amil Zakat Nasional (BAZNAS) Provinsi Sumatra Selatan - Suci Aulia Romadhona; Qodariah Barkah; Peny Cahaya Azwari (Jurnal Ilmiah Ekonomi Islam, 2023)
Scholarships provide assistance for those who are still in school or college so they can complete their assigments and seek knowledge until they are finished. This assistance is usually in the studying for the desired education. The national Amil Zakat Agency for South Sumatra Province has a program, namely scholarships. After the Covid-19 pandemic, all activities were hampered, both in the fields of education and the economy, among many others. This study uses documentation. The results of this study indicate that the impact of channeling zakat funds in the form of schilarships is that they can help and overcome education costs for students who have effectiveness off distributing zakat funds in the form of scholarships during the Covid-19 pandemic is very effective because it is right in target and also very helpful, especially during the Covid-19 pandemic, which has caused many effects, such as job loss, which has caused people to face difficulties in the economy. The similarities and differences in the distribution of zakat funds in the form of scholarships before and after the Covid-19 pandemic, namely, the similarities, are that they are both running and implemented. Then the quota of scholarship recipients remains the same without being reduced. The difference is that there i no visible difference, or it ean be said that there was no difference either before or after the Covid-19 pandemic.